2020
DOI: 10.4218/etrij.2019-0294
|View full text |Cite
|
Sign up to set email alerts
|

Resource‐efficient load‐balancing framework for cloud data center networks

Abstract: Cloud computing has drastically reduced the price of computing resources through the use of virtualized resources that are shared among users. However, the established large cloud data centers have a large carbon footprint owing to their excessive power consumption. Inefficiency in resource utilization and power consumption results in the low fiscal gain of service providers. Therefore, data centers should adopt an effective resource‐management approach. In this paper, we present a novel load‐balancing framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…Chen et al [31] consider the problem of LB in a multi-objective framework, where initially the problem of resource allocation for emergent demands is resolved. In [32] the authors present a loadbalancing framework with the objective of minimizing the operational cost of data centers using a genetic algorithm for resource allocation. Weight factors have also been employed for resources like physical memory, bandwidth, number of processors, and processor speed [33].…”
Section: Related Workmentioning
confidence: 99%
“…Chen et al [31] consider the problem of LB in a multi-objective framework, where initially the problem of resource allocation for emergent demands is resolved. In [32] the authors present a loadbalancing framework with the objective of minimizing the operational cost of data centers using a genetic algorithm for resource allocation. Weight factors have also been employed for resources like physical memory, bandwidth, number of processors, and processor speed [33].…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [31] concluded that certain bin-packing strategies were considered for renting 3 Wireless Communications and Mobile Computing servers in the cloud. Some approaches have been studied for connecting the bin-packing problem to the centralized scheduling problem [29,30,[32][33][34][35][36][37].…”
Section: Related Workmentioning
confidence: 99%
“…20-36 repeat till accomplishment of termination criteria (by utilizing fourth stage of Section 4).A), where step 21 evaluates cost values of four objectives using Eqs. ( 5), ( 6), (9), and (11) associated to each solution of g th iteration (i.e., ψ g ). Step…”
Section: B Operational Design and Complexity Computationmentioning
confidence: 99%
“…To meet the ever-growing and dynamic demand of users, more and more VMs are deployed on a large number of servers and cooling devices are installed at data centre that account for high power consumption [6], [7], [8]. The VM placement (VMP) has a crucial impact on resource utilization, power consumption, and the overall operational cost of the data centre [9], [10], [11]. The inefficient VMP leads to under/over-utilized servers with increased power consumption and resource wastage.…”
Section: Introductionmentioning
confidence: 99%